ANALYSIS OF THE EFFECT OF LUNAR CYCLE ON LIQUID 45 (LQ45) STOCKS ON THE INDONESIA STOCK EXCHANGE (IDX) FOR THE PERIOD 2005-2020 - Fendi Pramono; Sautma Ronni Basana (Finance and Investment Program, School of Business and Management - Petra Christian University, 2022)
This study examines the impact of the moon phase in influencing investors' decisions to invest in the stock market. As an investor, market timing is needed to maximize the return on your investment. Fundamental and technical analysis cannot predict when investors can buy or sell shares to maximize profits. The research was conducted on stocks that never left the Liquid 45 from 2005 to 2020.